Interactive effect of temperature, pH and light intensity on biodesalination of seawater by Synechococcus sp. PCC 7002 and on the cyanobacteria growth - Azmi, Azlin Suhaida; Shakilla Sani, Fazrizatul; Ali, Fathilah; Mel, Maizirwan (Penerbit Akademia Baru, 2018)
Desalination allows to pipe viable water supply from ocean, the largest water resource, as potable water for drink and daily usage. The technology such as thermal distillation and membrane separation technology requires intense energy source. Almost all desalination plants using fossil fuel as their primary energy source, which leads to many challenges. Marine-euryhaline Synechococcus sp. strain PCC 7002, on the other hand, is one of the potential cyanobacteria that may contribute to the development and advancement in water treatment field. These cyanobacteria are able to generate a huge amount of biomass and producing fresh water (low-salt saline water). Thus, this leads the study to investigate the influence of process parameters on biodesalination by Synechococcus sp. PCC 7002 associate to growth rate of the cyanobacteria. The results showed that temperature, light intensity and pH play important role in sodium reduction. More than 50% of salinity reduction was obtained at optimum condition. Interactive effects between selected factors concluded that higher salinity removal was observed at temperature of 36oC with the pH of 10 and light intensity of 3500 lux. However, the growth is contrast to biodesalination. Interaction effect between temperature-pH, suggested that the growth prefer near neutral condition regardless of the temperature. When temperature interacts with light intensity, inverse relation of these two factors resulted of higher growth rates. Further study is required to understand biodesalination by Synechococcus sp. and its growth. Nevertheless, the study has shown that biodesalination by Synechococcus sp. has the potential in biodesallination process and integration with current technology for potable water source can be further investigated.